Content Analysis of Sexual Violence News on Twitter - Deti Nudiati; Sardin Sardin; Alyssa Nurwahidah; Billy Hari Pamungka; Marianne Laksana Jati (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2023)
The number of sexual violence cases in Indonesia is increasing every year. However, only a few of the victims are willing to speak out, including on social media sites like Twitter. The study aims to determine the tendency of victims to speak by measuring the tendency of news written on Twitter through news headlines, news writers, types of sexual violence, responses to news of sexual violence revealed on Twitter, and the sustainability of the case before the law. This research method uses quantitative content analysis methods. The results of research on the tendency of sexual violence news content on Twitter show that the majority of news published does not meet the main elements of the news, and the most revealed type of violence is mental and physical sexual harassment, compared to other types of violence such as physical, sexual harassment only, sexual assault in the form of rape, prosecution or coercion of sexual activities, and forced sexual activities. Victims dominate the news writers who tell their stories via Twitter, and the rest are written by friends or relatives related to the victims. Of all the violent news stories examined, not one received a negative response. The majority responded positively, and very few responded neutrally. After the news was published on Twitter, only one case out of four continued to be processed legally. Research findings show that framing news on social media can influence people's perceptions and attitudes toward important issues